2020
DOI: 10.3390/jcm9082662
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulopathy Is Associated with the Outcome of Persistent Inflammation, Immunosuppression and Catabolism Syndrome

Abstract: Persistent inflammation, immunosuppression and catabolism syndrome (PIICS) often occur after critical care. Disseminated intravascular coagulation (DIC) is expected to be associated independently with PIICS development. We retrospectively analyzed 5397 patients admitted to the Hitachi General Hospital emergency and critical care center during four years. We classified PIICS as C-reactive protein > 3.0 mg/dL or albumin < 3.0 g/dL or lymphocyte count < 800/μL on day 14. Prolonged hospital stay (>14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
1
18
2
Order By: Relevance
“…Nakamura et al reported that age, sex, sepsis, albumin level, lymphocyte count, Hb and HbA1c levels, Cr level, and overt DIC were signi cantly associated with PIICS [5]. Thus, the results of the present study are consistent with their ndings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nakamura et al reported that age, sex, sepsis, albumin level, lymphocyte count, Hb and HbA1c levels, Cr level, and overt DIC were signi cantly associated with PIICS [5]. Thus, the results of the present study are consistent with their ndings.…”
Section: Discussionsupporting
confidence: 92%
“…To analyze the factors related to the onset of PIICS, univariate analysis was performed with PIICS as the objective variable and with each of the following factors as explanatory variables: patient pro le (age, sex, height, and weight); factors involved in the diagnosis of PIICS (CRP and albumin levels and lymphocyte count); factors reported as potential risk factors in previous studies (sepsis; Cr, Hb, and HbA1c levels, overt DIC, and APACHE II score) [5]; history of steroid use; and blood transfusion (RBC, FFP, PLT). Next, a multivariate logistic regression analysis was performed with PIICS as the objective variable and all the above variables as explanatory variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients experience chronic inflammation, which is also known as persistent inflammation, immunosuppression, and catabolism syndrome [ 90 ]. This condition may be caused by various conditions including disseminated intravascular coagulopathy [ 91 ] and electrolyte imbalance [ 92 ]. Chronic inflammation is known to cause muscle atrophy [ 93 ].…”
Section: Picsmentioning
confidence: 99%
“…Some patients experience chronic inflammation, which is called the Persistent Inflammation, Immunosuppression, and Catabolism Syndrome [71]. This condition may be caused by various conditions including disseminated intravascular coagulopathy [72] and electrolyte imbalance [73]. Chronic inflammation is known to cause muscle atrophy [74].…”
Section: Picsmentioning
confidence: 99%